IMPLEMENTASI STRATEGI PEMBELAJARAN THINK PAIR SHARE PADA MTS KELAS VII YAYASAN PENDIDIKAN AS-SHOFA - Arlina; Friska Pratiwi; Fathinatul Wafiqah Lubis; Fakhry Muhammad Erde (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to determine the application of the Think Pair Share learning strategy at MTS Class VII of the As-Shofa Education Foundation, running as expected or not. This research reveals based on what happens in the field, namely when the Think Pair Share strategy is applied in the classroom. The type of research used in this study is a type of qualitative research method. Data collection techniques include observation, documentation, and interviews. The research data analysis process in this study has three components, namely data reduction, data presentation, and drawing conclusions. The validity techniques in this research are lingering, lengthy and triangulation. The results of this study indicate that the Think Pair Share learning strategy applied at school attracts students' reactions to learning, namely: fun, lessons are easier to understand, and train to be able to work together and respect the opinions of others. The results also show the obstacles to the implementation of Think Pair Share, namely: small classrooms, as well as inadequate facilities hinder the application of this strategy and require a lot of time in its application.